2016
DOI: 10.1016/j.accfor.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Creating and reinforcing discrimination: The controversial role of accounting in bank lending

Abstract: This paper examines the controversial role played by accounting within the discriminatory bank-lending practices of a privately owned bank in Sri Lanka. It reports on an analytical auto-ethnography (during the period 1994-2004) coupled with follow-up interviews and reiterated analyses. Data were analysed using Pierre Bourdieu's concepts of field, capital, habitus and symbolic violence. The empirical findings of the paper illustrate how key capitals at macro levels (social, cultural and symbolic) are mobilised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As outlined in our discussion, academics need to renew their focus on SME financing. Public and private financial sectors in developing economies need to renew and improve their efforts to enable better access to financing for SMEs, and work to eradicate discriminatory lending in these countries (Saliya and Jayasinghe 2016). Last year, the announcement of the European Investment Bank (EIB) and Spanish bank Banco Bilbao Vizcaya Argentaria (BBVA) to make 600 million euros available for SMEs in Spain is a step in the right direction.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in our discussion, academics need to renew their focus on SME financing. Public and private financial sectors in developing economies need to renew and improve their efforts to enable better access to financing for SMEs, and work to eradicate discriminatory lending in these countries (Saliya and Jayasinghe 2016). Last year, the announcement of the European Investment Bank (EIB) and Spanish bank Banco Bilbao Vizcaya Argentaria (BBVA) to make 600 million euros available for SMEs in Spain is a step in the right direction.…”
Section: Discussionmentioning
confidence: 99%
“…Many theories have been published on psychological and sociological factors to explain individual investors' investment decisions (Clark-Murphy and Soutar 2004;Kumar and Lim 2008;Seasholes and Zhu 2010;Korniotis and Kumar 2011;Barber and Odean 2011). Sarwar and Afaf (2016) showed that psychological factors have stronger effects on investors' decision making than do economic factors. However, the potential mediating role of psychosocial resources has been rarely explored in relation to SMP behavior.…”
Section: Methodology and Experimental Designmentioning
confidence: 99%
“…Another issue is the accounting profession's racial practices, based on colour and ethnicity Huang et al 2016;Hayes and Jacobs 2017). Few scholars have shown any evidence about the relationship between accounting and racial discrimination based on class or group Tyson et al 2004;Saliya and Jayasinghe 2016;. Notably, some scholars argue that counter-accounts are not entirely neutral in supporting social justice, because they usually emerge from specific hegemonic interests.…”
Section: Literature Focusmentioning
confidence: 99%